The supply base and its complexity: Implications for transaction costs, risks, responsiveness, and innovation - Choi, Thomas Y.; Krause, Daniel R. (Journal of Operations Management, 2006)
AbstractA supply base is defined as the portion of a supply network that is actively managed by a buying company. The buying company, referred to as the focal company, manages the suppliers in the supply base through contracts and purchasing of parts, materials, and services. To facilitate better management of a supply base, we observe “complexity” as a key area of managerial consideration and apply the literature on complexity to the supply base. Supply base complexity is conceptualized in three dimensions: (1) the number of suppliers in the supply base, (2) the degree of differentiation among these suppliers, and (3) the level of inter‐relationships among the suppliers. Four propositions have been formulated in terms of four major areas of research within supply chain management—transaction costs, supply risk, supplier responsiveness, and supplier innovation. Corollary propositions are also stated. Although a reduction in complexity may lead to lower transaction costs and increased supplier responsiveness, in certain circumstances it may also increase supply risk and reduce supplier innovation. Therefore, reducing supply base complexity in general may be a cost‐efficient approach, but blindly reducing it may potentially decrease the buying company's overall competitiveness.